Transformasi Sosial dan Pendidikan: Pemberdayaan Masyarakat Dusun Wedegan melalui Program Pendidikan dan Keagamaan - Moh. Holil Baitaputra; Bustomi Arisandi; Zainal Hakim; M. Imamul Muttaqin; Tri Wahyudi Ramdhan; Bahrul Ulum (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Community service in Wedegan Hamlet, Sambikerep Village, Rejoso Subdistrict, Nganjuk Regency aims to improve the quality of education and religious life in order to strengthen community empowerment. This program involves a participatory approach, in which the community plays an active role in planning and implementing various activities that are relevant to their needs. The main focus of this program is the revitalization of religious activities in local mosques and prayer rooms, improving the quality of non-formal education through tutoring, and developing social skills for teenagers through tambourine art training. In addition, this program also seeks to raise community awareness of the importance of education and religious activities as an integral part of daily life. The results achieved show an increase in community participation in religious activities, improved quality of children's education through tutoring, and the creation of more harmonious social relationships among residents. Community empowerment through this program has made an important contribution to creating sustainable social change at the village level.